Support for renewable energy: The case of wind power - Robert Germeshausen; Sven Heim; Ulrich J. Wagner (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
Successful decarbonization of the electricity sector hinges on the support of the public, which is at risk when electricity generation emits local externalities. This paper estimates the impact of wind turbine deployment on granular measures of revealed preferences for renewable electricity in product and political markets. We address endogenous siting of turbines with a novel IV approach that exploits quasi-experimental variation in profitability. We find that nearby wind turbines significantly reduce citizens' support, but this effect quickly fades with distance from the site. Our results shed light on how distance requirements and financial participation could enhance support for renewables.
Keywords: D12; D72; Q42; Q50; 330; Renewable energy; Wind power; Public support; Elections; Externalities